APPLICATION OF APRIORIC ALGORITHM IN ORDERING PRINTING MATERIALS - Ita Sari Nova Sitompul; Volvo Sihombing; Masrizal (Sean Institute, 2021)
Wendy Printing is one of the printers that collaborates with Labuhan Batu University, especially in the Computer Science faculty, Wendy's printing is located on the Jalan setia budi intersection of Labuhan Batu University campus. Wendy printing leaders and employees sometimes have difficulty knowing how many teaching materials are printed in one transaction, so that Wendy's printing leaders are still manual / speculative in printing teaching materials. The application of data mining for ordering teaching materials at the faculty of computer science at Labuhan Batu University in the wendy print can produce association rules that can be seen and analyzed for the results, so that the print leader can see the frequency of teaching materials that often occur in every transaction. Therefore, analysis and testing are carried out,